Copolymerized antibacterial far-infrared polyester and preparation method thereof

By performing surface modification and copolymerization reaction on the far-infrared powder and connecting it with the polyester macromolecular chain, the problem of uneven dispersion of far-infrared powder in the polyester matrix is ​​solved, the uniform dispersion and stability of polyester are achieved, and the mechanical properties are improved.

CN119615403APending Publication Date: 2025-03-14BEIJING AEROSPACE KAIEN NEW & ADVANCED MATERIAL CO LTD +2

Patent Information

Application Number
CN202311177458.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, far-infrared inorganic functional powders are unevenly dispersed in the polyester matrix, resulting in problems such as stiff wires and floating wires in polyester spinning processing, and affecting the mechanical properties of polyester.

Method used

By performing surface modification treatment on the far-infrared powder, the far-infrared powder is connected with the far-infrared powder by an aminosilane coupling agent to generate a modified far-infrared powder, and it is connected to the polyester macromolecular chain through copolymerization reaction to form a copolyester.

Benefits of technology

The uniform dispersion and stability of far-infrared powder in the polyester matrix is ​​achieved, and the problems of rigid and floating wires in polyester spinning are avoided, and the mechanical properties of polyester are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615403A_ABST
    Figure CN119615403A_ABST
Patent Text Reader

Abstract

The invention discloses a copolymerized antibacterial far-infrared polyester and a preparation method thereof, the preparation method comprises the following steps: (1) adding an absolute ethyl alcohol solution of an amino silane coupling agent into a first solvent dispersed with far-infrared powder, and heating for reaction to prepare I-type modified far-infrared powder; (2) heating and reacting the I-type modified far infrared powder, p-carboxybenzaldehyde and a buffering agent in a second solvent to prepare II-type modified far infrared powder; and (3) mixing terephthalic acid, ethylene glycol, a catalyst and the II-type modified far infrared powder, carrying out condensation polymerization on the mixture, discharging, and cooling to obtain the antibacterial far infrared copolyester, and (4) carrying out melt spinning on the antibacterial far-infrared copolyester to obtain the copolymerized antibacterial far-infrared polyester. The antibacterial far-infrared polyester prepared by the invention contains the Schiff base structure and the far-infrared powder which are connected with a polyester molecular chain through covalent bonds, so that the polyester has antibacterial and far-infrared functions, and meanwhile, the mechanical property of the polyester is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthetic fiber preparation, and in particular relates to a copolymerized antibacterial far-infrared polyester and a preparation method thereof. Background Art

[0002] Polyester, also known as polyester fiber, is generally made of polyethylene terephthalate (PET) made by polycondensation of terephthalic acid and ethylene glycol monomers, and then processed by melt spinning. Polyester fiber has many excellent properties, such as high breaking strength, high modulus, good elasticity, good heat resistance and shape retention, etc. It can be widely used in various clothing and decorative materials. In industry, it can also be used as conveyor belts, tents, cords, electrical insulation materials, cables, fishing nets, filter cloths, etc.

[0003] As people's living standards improve, they pay more and more attention to issues such as environment, hygiene, life health, and health care. In order to expand the scope of application of polyester in these fields and increase the added value of polyester, it is urgent to study the modification of polyester in antibacterial and far infrared health functions. Inorganic functional powders such as tourmaline and Tai Chi stone have health functions such as far infrared. At present, there are many studies on using these inorganic functional powders to provide health functions for polyester.

[0004] For example, Chinese patent application number CN201110425503.X discloses a production process for far-infrared polyester staple fibers, in which far-infrared masterbatches are added during the melt spinning of recycled polyester chips, and the far-infrared masterbatches contain 19%-21% far-infrared ceramic powder.

[0005] A Chinese patent application numbered CN201510966957.6 discloses a method for manufacturing an antibacterial far-infrared health-care polyester fiber. The antibacterial far-infrared health-care polyester fiber is prepared by adding antibacterial and far-infrared material masterbatches during spinning. The antibacterial material is a sodium zirconium phosphate copper-loaded antibacterial material, and the far-infrared material is a Tai Chi stone far-infrared material. The antibacterial far-infrared health-care polyester fiber can be prepared by online addition spinning of antibacterial powder and Tai Chi stone far-infrared powder, or by spinning antibacterial powder and far-infrared powder into masterbatches, mixing them with polyester chips, and then spinning them.

[0006] The above methods all improve the functionality of polyester by blending far-infrared inorganic functional powders with polyester matrix. In order to improve the dispersibility of far-infrared inorganic functional powders in polyester matrix, generally, a number of dispersants and other additives are added during the blending process, or the far-infrared inorganic functional powders are pre-treated before blending to change their surface properties. However, these methods all use the van der Waals force between far-infrared inorganic functional powders and polyester macromolecules to fuse and disperse each other. This force is very weak, and often causes the infrared inorganic functional powders to migrate continuously in the matrix or even agglomerate during polyester melt processing, resulting in uneven and unstable dispersion of the far-infrared inorganic functional powders in the polyester matrix, causing problems such as stiff silk and floating silk during spinning processing, and also affecting the mechanical properties and other properties of polyester yarns. Therefore, it is of great significance to develop a new method to add far-infrared inorganic functional powders to polyester matrix.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a copolymerized antibacterial far-infrared polyester and a preparation method, so that the far-infrared component is evenly dispersed in the polyester matrix and is not easy to migrate, thereby improving the mechanical properties of the polyester.

[0009] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0010] A method for preparing a copolymerized antibacterial far-infrared polyester comprises the following steps:

[0011] (1) dispersing the far-infrared powder into a first solvent, adding an anhydrous ethanol solution of an aminosilane coupling agent, reacting under heating conditions, washing and drying to obtain type I modified far-infrared powder;

[0012] (2) adding p-carboxybenzaldehyde and a buffer, and the type I modified far-infrared powder obtained in step (1) to a second solvent, reacting under heating conditions, washing and drying to obtain the type II modified far-infrared powder;

[0013] (3) mixing terephthalic acid, ethylene glycol, a catalyst, and the type II modified far-infrared powder obtained in step (2), subjecting the mixture to polycondensation, discharging the mixture, and cooling the mixture to obtain an antibacterial far-infrared copolyester;

[0014] (4) The antibacterial far-infrared copolyester prepared in step (3) is melt-spinned to obtain copolymerized antibacterial far-infrared polyester.

[0015] In the present invention, the far-infrared powder is firstly subjected to surface modification treatment using an aminosilane coupling agent containing an amine group, thereby connecting the aminosilane coupling agent and the far-infrared powder using a silicon-oxygen covalent bond to obtain a type I modified far-infrared powder. Then, the aldehyde group of carboxyl formaldehyde and the amine group of the aminosilane coupling agent are reacted to generate a Schiff base structure with antibacterial function, and at the same time, the carboxyl formaldehyde is connected to the surface of the far-infrared powder in the form of a covalent bond to obtain a type II modified far-infrared powder, thereby making the surface of the far-infrared powder rich in benzoic acid structure. The carboxyl activity in the above-mentioned benzoic acid structure is equivalent to the carboxyl activity in terephthalic acid, and the obtained type II modified far-infrared powder can undergo copolymerization reaction with ethylene glycol together with terephthalic acid, thereby connecting the far-infrared powder and the Schiff base structure in series to the polyester macromolecular chain through a covalent bond.

[0016] In this way, in the copolyester prepared by copolymerization, the polyester macromolecule chain is connected with far-infrared powder and Schiff base structure with antibacterial function by covalent bonds. The above copolyester is further used for melt spinning. Since the covalent bond connection method is significantly stronger than the connection method through intermolecular van der Waals force, and the same far-infrared powder particles are generally connected to multiple polyester macromolecule chains, the force between polyester macromolecule chains becomes stronger, so that the far-infrared powder that has been dispersed in the copolymerization process can only move around the polyester macromolecule to which it is connected, and it is not easy to migrate. At the same time, the particle size of the far-infrared powder is larger than the diameter of the polyester macromolecule chain, so the polyester macromolecule itself also forms an obstacle to the migration of the far-infrared powder, making different far-infrared powder particles unable to approach each other, preventing agglomeration. Therefore, it can be ensured that during the melt spinning process, the far-infrared powder is dispersed evenly and stably in the polyester matrix, avoiding problems such as stiff fibers and floating fibers during the melt spinning process, reducing restrictions on processing conditions, and at the same time, the mechanical properties of the polyester prepared, such as breaking strength and breaking elongation, are improved compared to the polyester prepared by traditional blending methods.

[0017] Furthermore, in step (1), the first solvent in which the far-infrared powder is dispersed is heated to 60-80° C. under stirring, and then an anhydrous ethanol solution containing an aminosilane coupling agent is slowly added dropwise, and the stirring reaction is continued for 2-3 hours. After the reaction is completed, the mixture is cooled, washed with anhydrous ethanol, and then vacuum dried at 60-80° C. for 2-3 hours to obtain type I modified far-infrared powder;

[0018] Preferably, the aminosilane coupling agent is silane coupling agent KH550; in the anhydrous ethanol solution of the aminosilane coupling agent, the mass concentration of silane coupling agent KH550 is 15% to 25%, preferably 20%;

[0019] Preferably, after adding the far-infrared powder to the first solvent and stirring evenly, the powder is dispersed by ultrasonic treatment for 20 to 30 minutes.

[0020] In the above scheme, the far-infrared powder is first dispersed in the first solvent, and then the anhydrous ethanol solution of the silane coupling agent KH550 is added dropwise under heating and stirring conditions. The dropping method is conducive to controlling the addition speed of the silane coupling agent KH550, thereby facilitating a more complete reaction between the silane coupling agent KH550 and the far-infrared powder. Dispersing by ultrasonic treatment can enhance the uniformity of the dispersion of the far-infrared powder in the first solvent.

[0021] Furthermore, the mass ratio of the far-infrared powder, the first solvent and the anhydrous ethanol solution of the silane coupling agent KH550 is 1:5-6:1.5-2;

[0022] Preferably, the far-infrared powder is tourmaline powder, and the particle size of the tourmaline powder is preferably 100 to 200 nm;

[0023] Preferably, the first solvent is deionized water.

[0024] In the present invention, the above raw material ratio is adopted to achieve a better surface modification effect on the far-infrared powder. By controlling the particle size of the tourmaline powder within the range of 100 to 200 nm, it is easier to prevent the tourmaline powder from agglomerating during the melt spinning process, thereby ensuring the mechanical properties of the obtained polyester.

[0025] Furthermore, in step (2), the reaction system is heated to 30-40° C. under nitrogen protection, reacted for 6-8 hours, filtered after the reaction is completed, washed with methanol, and then vacuum dried at 60-80° C. for 2-3 hours to obtain type II modified far-infrared powder;

[0026] Preferably, the buffer is triethylamine;

[0027] Preferably, the type I modified far-infrared powder, p-carboxybenzaldehyde and buffer are added to the second solvent in sequence, and then heating is started to react.

[0028] Furthermore, the mass ratio of the type I modified far-infrared powder, p-carboxybenzaldehyde, buffer and the second solvent is 1: 0.2-0.4: 0.3-0.5: 30-50;

[0029] Preferably, the second solvent is methanol.

[0030] In the present invention, by controlling the reaction temperature, reaction time, and reactant ratio within the above range, the amino group of the type I modified far-infrared powder can fully react with the aldehyde group of the carboxyl formaldehyde. On the one hand, the content of the Schiff base structure in the prepared polyester is increased, thereby ensuring the antibacterial property of the polyester, and on the other hand, the content of the benzoic acid structure on the surface of the far-infrared powder is increased, thereby enhancing the bonding firmness between the far-infrared powder and the polyester macromolecular chain.

[0031] Further, in step (3), the polycondensation reaction comprises an esterification stage and a polycondensation stage performed sequentially;

[0032] The reaction temperature of the esterification stage is 240-260° C., the reaction pressure is 0.18-0.25 MPa, and the reaction time is 3-4 hours; the reaction temperature of the polycondensation stage is 275-285° C., the reaction pressure is 60-200 Pa, and the reaction time is 2-3 hours.

[0033] Furthermore, in step (3), the mass ratio of terephthalic acid, catalyst, type II modified far-infrared powder and ethylene glycol is 1: 0.0003-0.0005: 0.04-0.06: 0.6-0.7;

[0034] Preferably, the catalyst is antimony glycolate.

[0035] In the above scheme, by controlling the ratio of the reactants, the final polyester can achieve a balance between the antibacterial and far-infrared properties and the mechanical properties.

[0036] Furthermore, in step (3), terephthalic acid, catalyst, and type II modified far-infrared powder are sequentially added to ethylene glycol for slurry mixing, and the uniformly mixed mixture is transferred to a reactor for polycondensation reaction.

[0037] Furthermore, in step (4), the process conditions of the melt spinning include:

[0038] The screw extrusion temperature is 250-270℃ in zone 1, 280-285℃ in zone 2, 280-290℃ in zone 3, and 285-295℃ in zone 4;

[0039] The box temperature is 285-295°C, the spinning pressure is 10-12MPa, the side blowing speed is 0.4-0.5m / s, the oiling rate is 5%-15%, and the spinning speed is 4000-4500m / s;

[0040] Preferably, the antibacterial far-infrared copolyester obtained in step (3) is vacuum dried at 120-130° C. for 6-8 hours and then melt-spun.

[0041] A copolymerized antibacterial far-infrared polyester comprises a polyester matrix, far-infrared powder and a Schiff base structure, wherein the surface of the far-infrared powder is connected with a modified group; the modified group on the surface of the far-infrared powder is connected to the Schiff base structure by a covalent bond, and the Schiff base structure is connected to the molecular chain of the polyester matrix by a covalent bond;

[0042] Preferably, the copolymerized antibacterial far-infrared polyester is prepared by the above-mentioned method for preparing the copolymerized antibacterial far-infrared polyester.

[0043] In the above-mentioned antibacterial far-infrared polyester, the far-infrared powder is used to provide the far-infrared function, the Schiff base structure is used to provide the antibacterial function, and the molecular chain of the polyester matrix connects the above-mentioned Schiff base structure and the far-infrared powder through a covalent bond, which is conducive to maintaining the good dispersion of the far-infrared powder in the polyester matrix. In this way, the antibacterial far-infrared fiber has good mechanical properties while having antibacterial and far-infrared functions, thereby broadening the application scenarios.

[0044] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.

[0045] 1. The preparation method of the present invention performs surface modification on far-infrared powder, connects Schiff base structure and benzoic acid structure on the surface of far-infrared powder, and the Schiff base structure and benzoic acid structure are connected by covalent bond, and then the type II modified far-infrared powder obtained after surface modification is copolymerized with terephthalic acid and ethylene glycol, and the far-infrared powder and Schiff base structure can be connected in series to the polyester macromolecular chain by covalent bond. Thus, compared with the traditional melt blending spinning method, the present invention can maintain uniform and stable dispersion without agglomeration during the melt spinning process due to the stronger binding force provided by the covalent bond, which not only avoids the problems of stiff silk and floating silk in the melt spinning process, but also improves the mechanical properties of the obtained antibacterial far-infrared polyester.

[0046] 2. The obtained antibacterial far-infrared polyester has both antibacterial and far-infrared functions and better mechanical properties, thus having a wider range of applications.

[0047] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0049] Figure 1 This is a reaction formula for preparing type II modified tourmaline powder by reacting type I modified tourmaline powder and p-carboxybenzaldehyde in a specific embodiment of the present invention.

[0050] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0052] The invention provides a preparation method of copolymerized antibacterial far-infrared polyester and a copolymerized antibacterial far-infrared fiber.

[0053] Wherein, the preparation method comprises the following steps:

[0054] (1) dispersing the far-infrared powder into a first solvent and an anhydrous ethanol solution of an aminosilane coupling agent, reacting under heating conditions, washing and drying to obtain type I modified far-infrared powder;

[0055] (2) adding p-carboxybenzaldehyde and a buffer, and the type I modified far-infrared powder obtained in step (1) to a second solvent, reacting under heating conditions, washing and drying to obtain the type II modified far-infrared powder;

[0056] (3) mixing terephthalic acid, ethylene glycol, a catalyst, and the second modified far-infrared powder obtained in step (2), subjecting the mixture to polycondensation, discharging the mixture, and cooling the mixture to obtain an antibacterial far-infrared copolyester;

[0057] (4) The antibacterial far-infrared copolyester prepared in step (3) is melt-spinned to obtain copolymerized antibacterial far-infrared polyester.

[0058] As a specific embodiment of the present invention, the far-infrared powder is tourmaline powder, and the preparation method comprises the following steps:

[0059] (1) adding tourmaline powder with a particle size of 100 to 200 nm to deionized water and stirring evenly, ultrasonically treating for 20 to 30 minutes, and then heating to 60 to 80° C. under stirring, and then slowly dropping an anhydrous ethanol solution containing a silane coupling agent KH550 with a mass concentration of 20%, and continuing to stir and react for 2 to 3 hours. After the reaction is completed, cooling, washing with anhydrous ethanol, and then vacuum drying at a temperature of 60 to 80° C. for 2 to 3 hours to obtain type I modified tourmaline powder; in this step, the mass ratio of tourmaline powder, deionized water and anhydrous ethanol solution of silane coupling agent KH550 is 1:5 to 6:1.5 to 2;

[0060] (2) under continuous stirring, the type I modified tourmaline powder obtained in step (1), p-carboxybenzaldehyde and triethylamine are added to methanol in sequence, wherein the mass ratio of type I modified tourmaline powder, p-carboxybenzaldehyde, triethylamine and methanol is 1:0.2-0.4:0.3-0.5:30-50, and then heated to 30-40°C under nitrogen protection for reaction for 6-8h. After the reaction is completed, the mixture is filtered, washed thoroughly with methanol, and then vacuum dried at 60-80°C for 2-3h to obtain type II modified tourmaline powder. The reaction formula of this step is as follows: Figure 1 As shown;

[0061] (3) adding terephthalic acid, ethylene glycol antimony catalyst and type II modified far-infrared powder obtained in step (2) to ethylene glycol in sequence for slurry mixing, wherein the mass ratio of terephthalic acid, ethylene glycol antimony, type II modified tourmaline powder and ethylene glycol is 1: 0.0003-0.0005: 0.04-0.06: 0.6-0.7, and transferring to a reaction kettle for polycondensation reaction after being evenly mixed. The polycondensation reaction includes an esterification stage and a polycondensation stage carried out in sequence, wherein the reaction temperature of the esterification stage is 240-260° C., the reaction pressure is 0.18-0.25 MPa, and the reaction time is 3-4 h, and the reaction temperature of the polycondensation stage is 275-285° C., the reaction pressure is 60-200 Pa, and the reaction time is 2-3 h. After the reaction is completed, the material is discharged, water-cooled and pelletized to obtain antibacterial far-infrared copolyester chips;

[0062] (4) vacuum drying the antibacterial far-infrared copolyester chips obtained in step (3) at a temperature of 120-130° C. for 6-8 h, and then melt spinning to obtain copolymerized antibacterial far-infrared polyester; wherein the process conditions of melt spinning are as follows: the screw extrusion temperature is 250-270° C. for zone 1, 280-285° C. for zone 2, 280-290° C. for zone 3, and 285-295° C. for zone 4; the box temperature is 285-295° C.; the spinning pressure is 10-12 MPa; the side blowing speed is 0.4-0.5 m / s; the oiling rate is 5%-15%; and the spinning speed is 4000-4500 m / s.

[0063] Example 1

[0064] (1) adding tourmaline powder with a diameter of 100 nm to deionized water and stirring evenly, ultrasonicating for 20 minutes, and then heating to 60° C. under stirring, and then slowly dropping an anhydrous ethanol solution containing a silane coupling agent KH550 with a mass concentration of 20%, and continuing to stir and react for 2 hours. After the reaction is completed, cooling, washing with anhydrous ethanol, and then vacuum drying at 60° C. for 2 hours to obtain type I modified tourmaline powder; in this step, the mass ratio of tourmaline powder, deionized water and anhydrous ethanol solution of silane coupling agent KH550 is 1:6:2;

[0065] (2) under continuous stirring, the type I modified tourmaline powder prepared in step (1), p-carboxybenzaldehyde and triethylamine are added to methanol in sequence, wherein the mass ratio of type I modified tourmaline powder, p-carboxybenzaldehyde, triethylamine and methanol is 1:0.4:0.5:50, and then heated to 30°C under nitrogen protection for reaction for 6 hours. After the reaction is completed, the mixture is filtered, washed with methanol, and then vacuum dried at 60°C for 2 hours to obtain type II modified tourmaline powder;

[0066] (3) terephthalic acid, ethylene glycol antimony catalyst and type II modified tourmaline powder obtained in step (2) are sequentially mixed with ethylene glycol by beating, wherein the mass ratio of terephthalic acid, ethylene glycol antimony, type II modified tourmaline powder and ethylene glycol is 1:0.0003:0.04:0.6, and after being evenly mixed, they are transferred to a reactor for polycondensation reaction, wherein the polycondensation reaction includes an esterification stage and a polycondensation stage performed sequentially, wherein the reaction temperature of the esterification stage is 240°C, the reaction pressure is 0.18 MPa, and the reaction time is 3 h, and the reaction temperature of the polycondensation stage is 275°C, the reaction pressure is 60 Pa, and the reaction time is 2 h. After the reaction is completed, the material is discharged, water-cooled and pelletized to obtain antibacterial far-infrared copolyester chips;

[0067] (4) The antibacterial far-infrared copolyester chips obtained in step (3) are vacuum dried at 120° C. for 6 h, and then melt-spinned to obtain copolymerized antibacterial far-infrared polyester; wherein the process conditions for melt spinning are as follows: the screw extrusion temperature is 250° C. for zone 1, 280° C. for zone 2, 280° C. for zone 3, and 285° C. for zone 4; the box temperature is 285° C.; the spinning pressure is 10 MPa; the side blowing speed is 0.4 m / s; the oiling rate is 5%; and the spinning speed is 4000 m / s.

[0068] Example 2

[0069] (1) adding tourmaline powder with a diameter of 200 nm into deionized water and stirring evenly, ultrasonicating for 30 minutes, and then heating to 80° C. under stirring, and then slowly dropping an anhydrous ethanol solution containing a silane coupling agent KH550 with a mass concentration of 20%, and continuing to stir and react for 3 hours. After the reaction is completed, cooling, washing with anhydrous ethanol, and then vacuum drying at 80° C. for 3 hours to obtain type I modified tourmaline powder; in this step, the mass ratio of tourmaline powder, deionized water and anhydrous ethanol solution of silane coupling agent KH550 is 1:5:1.5;

[0070] (2) under continuous stirring, the type I modified tourmaline powder prepared in step (1), p-carboxybenzaldehyde and triethylamine are added to methanol in sequence, wherein the mass ratio of type I modified tourmaline powder, p-carboxybenzaldehyde, triethylamine and methanol is 1:0.2:0.3:30, and then heated to 40°C under nitrogen protection for reaction for 8 hours. After the reaction is completed, the mixture is filtered, washed with methanol, and then vacuum dried at 80°C for 3 hours to obtain type II modified tourmaline powder;

[0071] (3) terephthalic acid, ethylene glycol antimony catalyst and type II modified tourmaline powder obtained in step (2) are sequentially mixed with ethylene glycol by beating, wherein the mass ratio of terephthalic acid, ethylene glycol antimony, type II modified tourmaline powder and ethylene glycol is 1:0.0005:0.06:0.7, and after being evenly mixed, they are transferred to a reactor for polycondensation reaction, wherein the polycondensation reaction includes an esterification stage and a polycondensation stage performed sequentially, wherein the reaction temperature of the esterification stage is 260°C, the reaction pressure is 0.25 MPa, and the reaction time is 4 h, and the reaction temperature of the polycondensation stage is 285°C, the reaction pressure is 200 Pa, and the reaction time is 3 h. After the reaction is completed, the material is discharged, water-cooled and pelletized to obtain antibacterial far-infrared copolyester chips;

[0072] (4) The antibacterial far-infrared copolyester chips obtained in step (3) are vacuum dried at 130° C. for 8 h, and then melt-spinned to obtain copolymerized antibacterial far-infrared polyester; wherein the process conditions for melt spinning are as follows: the screw extrusion temperature is 270° C. for zone 1, 285° C. for zone 2, 290° C. for zone 3, and 295° C. for zone 4; the box temperature is 295° C.; the spinning pressure is 12 MPa; the side blowing speed is 0.5 m / s; the oiling rate is 15%; and the spinning speed is 4500 m / s.

[0073] Example 3

[0074] (1) adding tourmaline powder with a diameter of 150 nm to deionized water and stirring evenly, ultrasonicating for 25 minutes, and then heating to 70° C. under stirring, and then slowly dropping an anhydrous ethanol solution containing a silane coupling agent KH550 with a mass concentration of 20%, and continuing to stir and react for 3 hours. After the reaction is completed, cooling, washing with anhydrous ethanol, and then vacuum drying at 70° C. for 3 hours to obtain type I modified tourmaline powder; in this step, the mass ratio of tourmaline powder, deionized water and anhydrous ethanol solution of silane coupling agent KH550 is 1:5:2;

[0075] (2) under continuous stirring, the type I modified tourmaline powder prepared in step (1), p-carboxybenzaldehyde and triethylamine are added to methanol in sequence, wherein the mass ratio of type I modified tourmaline powder, p-carboxybenzaldehyde, triethylamine and methanol is 1:0.3:0.4:40, and then heated to 40°C under nitrogen protection for reaction for 7 hours. After the reaction is completed, the mixture is filtered, washed thoroughly with methanol, and then vacuum dried at 70°C for 3 hours to obtain type II modified tourmaline powder;

[0076] (3) terephthalic acid, ethylene glycol antimony catalyst and type II modified tourmaline powder obtained in step (2) are sequentially mixed with ethylene glycol by beating, wherein the mass ratio of terephthalic acid, ethylene glycol antimony, type II modified tourmaline powder and ethylene glycol is 1:0.0004:0.05:0.6, and after being evenly mixed, they are transferred to a reactor for polycondensation reaction, wherein the polycondensation reaction includes an esterification stage and a polycondensation stage performed sequentially, wherein the reaction temperature of the esterification stage is 250°C, the reaction pressure is 0.2MPa, and the reaction time is 4h, and the reaction temperature of the polycondensation stage is 280°C, the reaction pressure is 100Pa, and the reaction time is 3h. After the reaction is completed, the material is discharged, water-cooled and pelletized to obtain antibacterial far-infrared copolyester chips;

[0077] (4) The antibacterial far-infrared copolyester chips obtained in step (3) are vacuum dried at 130° C. for 6 h, and then melt-spinned to obtain copolymerized antibacterial far-infrared polyester; wherein the process conditions for melt spinning are as follows: the screw extrusion temperature is 260° C. for zone 1, 280° C. for zone 2, 285° C. for zone 3, and 290° C. for zone 4; the box temperature is 290° C.; the spinning pressure is 10 MPa; the side blowing speed is 0.5 m / s; the oiling rate is 12%; and the spinning speed is 4200 m / s.

[0078] Comparative Example 1

[0079] The difference between this comparative example and the above-mentioned Example 3 is that the type II modified tourmaline powder is not added, and conventional polyester chips are directly prepared using the comonomer raw material, and then melt-spinning is performed to obtain conventional polyester. The preparation method of this comparative example specifically includes the following steps:

[0080] (1) terephthalic acid and ethylene glycol antimony catalyst are sequentially slurried and mixed with ethylene glycol, wherein the mass ratio of terephthalic acid, ethylene glycol antimony and ethylene glycol is 1:0.0004:0.6, and after being evenly mixed, they are transferred to a reactor for polycondensation reaction, wherein the polycondensation reaction includes an esterification stage and a polycondensation stage performed sequentially, wherein the reaction temperature of the esterification stage is 250°C, the reaction pressure is 0.2 MPa, and the reaction time is 4 h, and the reaction temperature of the polycondensation stage is 280°C, the reaction pressure is 100 Pa, and the reaction time is 3 h, and after the reaction is completed, the material is discharged, water-cooled and pelletized to obtain conventional polyester chips;

[0081] (2) The conventional polyester chips obtained in step (1) are vacuum dried at 130° C. for 6 h, and then melt-spinned to obtain a conventional polyester; wherein the process conditions for melt spinning are as follows: the screw extrusion temperature is 260° C. for zone 1, 280° C. for zone 2, 285° C. for zone 3, and 290° C. for zone 4; the box temperature is 290° C.; the spinning pressure is 10 MPa; the side blowing speed is 0.5 m / s; the oiling rate is 12%; and the spinning speed is 4200 m / s.

[0082] Comparative Example 2

[0083] The difference between this comparative example and the above-mentioned Example 3 is that the type I modified tourmaline powder is directly added to the comonomer for in-situ blending to prepare the far-infrared copolyester chips, and then melt spinning is performed to obtain the far-infrared polyester. The preparation method of this comparative example specifically includes the following steps:

[0084] (1) adding tourmaline powder with a diameter of 150 nm to deionized water and stirring evenly, ultrasonicating for 25 minutes, and then heating to 70° C. under stirring, and then slowly dropping an anhydrous ethanol solution containing a silane coupling agent KH550 with a mass concentration of 20%, and continuing to stir and react for 3 hours. After the reaction is completed, cooling, washing with anhydrous ethanol, and then vacuum drying at 70° C. for 3 hours to obtain type I modified tourmaline powder; in this step, the mass ratio of tourmaline powder, deionized water and anhydrous ethanol solution of silane coupling agent KH550 is 1:5:2;

[0085] (2) terephthalic acid, ethylene glycol antimony catalyst and type I modified tourmaline powder obtained in step (1) are sequentially mixed with ethylene glycol, wherein the mass ratio of terephthalic acid, ethylene glycol antimony, type I modified tourmaline powder and ethylene glycol is 1:0.0004:0.05:0.6, and after being evenly mixed, they are transferred to a reactor for polycondensation reaction, wherein the polycondensation reaction includes an esterification stage and a polycondensation stage performed sequentially, wherein the reaction temperature of the esterification stage is 250°C, the reaction pressure is 0.2 MPa, and the reaction time is 4 h, and the reaction temperature of the polycondensation stage is 280°C, the reaction pressure is 100 Pa, and the reaction time is 3 h. After the reaction is completed, the material is discharged, water-cooled and pelletized to obtain far-infrared copolyester chips;

[0086] (3) The far-infrared copolyester chips obtained in step (2) are vacuum dried at 130° C. for 6 h, and then melt-spinned to obtain a far-infrared polyester; wherein the process conditions for melt spinning are as follows: the screw extrusion temperature is 260° C. for zone 1, 280° C. for zone 2, 285° C. for zone 3, and 290° C. for zone 4; the box temperature is 290° C.; the spinning pressure is 10 MPa; the side blowing speed is 0.5 m / s; the oiling rate is 12%; and the spinning speed is 4200 m / s.

[0087] Test Example 1

[0088] This test example tests the performance of the polyester prepared in the above embodiments and comparative examples, and the specific test method is as follows.

[0089] Far-infrared normal emissivity: Refer to the GB / T 30127-2013 "Testing and Evaluation of Far-infrared Performance of Textiles" test standard, and use the method of comparing with the standard black body to measure the far-infrared normal emissivity index. Specifically, 0.5g of polyester yarn is opened into a fluffy state and filled into an open cylindrical metal container with a diameter of 60mm and a height of 30mm. The fiber completely fills the container, and at least 3 specimens are taken for each sample; during the measurement, the test hot plate is heated to 34°C, and the far-infrared radiation intensity of the standard black body is first measured using a far-infrared radiation measurement system with a spectral response range covering the 5μm to 14μm band, and then the far-infrared radiation intensity of the sample is measured. By calculating the ratio of the radiation intensity of the sample to the standard black body, the far-infrared normal emissivity of the sample is obtained.

[0090] Antibacterial rate: Tested with reference to the oscillation method in FZ / T73023-2006 "Antibacterial knitwear Appendix D Antibacterial fabric test method", and the test bacteria used were Staphylococcus aureus and Escherichia coli. Specifically, first prepare a bacterial suspension, take an inoculation loop of bacteria and streak it on the nutrient agar medium of a plate, and culture it at 37°C for 24 hours; then prepare an inoculation suspension, draw 1mL from the bacterial suspension, add it to 9mL of nutrient broth, mix it evenly, then draw 1mL and add it to another 9mL of nutrient broth, mix it thoroughly, then draw 1mL and add it to another 9mL of 0.03mol / L PBS, mix it evenly, draw 5mL and add it to 45mL of 0.03mol / L PBS; prepare a sample, take 0.75g from the polyester sample to be tested, cut it into pieces, and sterilize it at 103kPa and 121°C for 15min; during the test, put the sample into a conical flask filled with 70mL PBS, use a pipette to add 5mL of inoculation suspension to the standard blank sample and the test sample respectively, mix it evenly, and take 1mL from each of the two flasks and put it into 9mL of 0.03mol / L PBS, mix well, then draw 1mL and transfer it to another 9mL 0.03mol / L PBS, shake well, draw 0.1mL from it and add it to two plates containing nutrient agar medium as parallel samples, culture at 37℃ for 24h, that is, "0" contact sample preparation, then use a pipette to add 5mL of inoculation suspension to the flask of antibacterial fabric sample, oscillate at 150r / min for 18h at 24℃, draw 1mL from each flask after the specified time and put it into 9mL 0.03mol / L PBS, dilute it by 10-fold dilution method, and then draw 0.1mL from each dilution test tube and put it into two plates as parallel samples, culture at 37℃ for 24h, and select the plates with appropriate dilution of 3 to 30 colonies for counting. The antibacterial rate is calculated according to the formula Y = (Wb-Wc) / Wb×100%, where:

[0091] Y——the antibacterial rate of the sample (%);

[0092] Wb——the concentration of viable bacteria in the flask after 18 hours of shaking contact with the standard blank sample, cfu / mL;

[0093] Wc——Concentration of viable bacteria in the flask (cfu / mL) after 18 hours of oscillation contact with polyester.

[0094] Breaking strength and breaking elongation: refer to GB / T14344-2008 "Test method for tensile properties of chemical fiber filaments" testing standard, and use YG020A electronic single yarn strength meter for testing; the test conditions are pre-tension (0.5±0.1) cN / tex, upper and lower chuck spacing 50cm, tensile speed 50cm / min, and test times 30 times.

[0095] The test results of this test example are shown in Table 1 below.

[0096] Table 1

[0097]

[0098] It can be seen that the antibacterial far-infrared polyester obtained in each embodiment has good far-infrared health care performance and antibacterial effect, and also has good mechanical properties, which is beneficial to broaden the application scope of the obtained polyester.

[0099] Comparative Example 1 is a process for preparing conventional polyester. Compared with Comparative Example 1, Example 3 has significantly improved far-infrared normal emissivity and antibacterial rates against Staphylococcus aureus and Escherichia coli. It can be seen that the antibacterial far-infrared polyester prepared by the preparation method of the present invention has good far-infrared health care performance and antibacterial effect, indicating that tourmaline micropowder and Schiff base structure are combined in the polyester matrix of the polyester. At the same time, the elongation at break of the antibacterial far-infrared polyester obtained in Example 3 is higher than that of the conventional polyester in Comparative Example 1, while the reduction in breaking strength compared with the conventional polyester is not obvious, indicating that the preparation method of the present invention effectively avoids the influence of the addition of tourmaline micropowder on the mechanical properties of polyester.

[0100] By comparing the test results of Example 3 and Comparative Example 2, it can be seen that the far-infrared normal emissivity levels of the two are comparable, but the far-infrared polyester of Comparative Example 2 is significantly weaker in antibacterial performance than that of Example 3 using the solution of the present invention. At the same time, the antibacterial far-infrared polyester obtained in Example 3 is significantly higher in breaking strength and breaking elongation than the far-infrared polyester obtained in Comparative Example 2. It can be seen that although the far-infrared polyester prepared in Comparative Example 2 has good far-infrared health care performance, it cannot avoid the problem of agglomeration of tourmaline micropowder during the melt spinning process due to the use of a blending method, which leads to a decrease in the mechanical properties of polyester, thereby limiting the processing conditions and scope of use of polyester.

[0101] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A method for preparing a copolymerized antibacterial far-infrared polyester, characterized in that: The following steps are involved: (1) dispersing the far-infrared powder into a first solvent, adding an anhydrous ethanol solution of an aminosilane coupling agent, reacting under heating conditions, washing and drying to obtain type I modified far-infrared powder; (2) adding p-carboxybenzaldehyde and a buffer, and the type I modified far-infrared powder obtained in step (1) to a second solvent, reacting under heating conditions, washing and drying to obtain the type II modified far-infrared powder; (3) mixing terephthalic acid, ethylene glycol, a catalyst, and the type II modified far-infrared powder obtained in step (2), subjecting the mixture to polycondensation, discharging the mixture, and cooling the mixture to obtain an antibacterial far-infrared copolyester; (4) The antibacterial far-infrared copolyester prepared in step (3) is melt-spinned to obtain copolymerized antibacterial far-infrared polyester.

2. The method for preparing the copolymerized antibacterial far-infrared polyester according to claim 1, characterized in that: In step (1), the first solvent in which the far-infrared powder is dispersed is heated to 60-80° C. under stirring, and then an anhydrous ethanol solution containing an aminosilane coupling agent is added dropwise, and the stirring reaction is continued for 2-3 hours. After the reaction is completed, the mixture is cooled, washed with anhydrous ethanol, and then vacuum dried at 60-80° C. for 2-3 hours to obtain type I modified far-infrared powder; Preferably, the aminosilane coupling agent is silane coupling agent KH550; in the anhydrous ethanol solution of the aminosilane coupling agent, the mass concentration of silane coupling agent KH550 is 15% to 25%, preferably 20%; Preferably, after the far-infrared powder is added to the first solvent and stirred evenly, it is dispersed by ultrasonic treatment for 20 to 30 minutes.

3. The method for preparing the copolymerized antibacterial far-infrared polyester according to claim 2, characterized in that: The mass ratio of the far-infrared powder, the first solvent and the anhydrous ethanol solution of the silane coupling agent KH550 is 1:5-6:1.5-2; Preferably, the far-infrared powder is tourmaline powder, and the particle size of the tourmaline powder is preferably 100 to 200 nm; Preferably, the first solvent is deionized water.

4. The method for preparing the copolymerized antibacterial far-infrared polyester according to any one of claims 1 to 3, characterized in that: In step (2), the reaction system is heated to 30-40° C. under nitrogen protection and reacted for 6-8 hours. After the reaction is completed, the mixture is filtered and washed with methanol, and then vacuum dried at 60-80° C. for 2-3 hours to obtain type II modified far-infrared powder; Preferably, the buffer is triethylamine; Preferably, the type I modified far-infrared powder, p-carboxybenzaldehyde and buffer are added to the second solvent in sequence, and then heating is started to react.

5. The method for preparing the copolymerized antibacterial far-infrared polyester according to claim 4, characterized in that: The mass ratio of the type I modified far-infrared powder, p-carboxybenzaldehyde, buffer and the second solvent is 1:0.2-0.4:0.3-0.5:30-50; Preferably, the second solvent is methanol.

6. The method for preparing the copolymerized antibacterial far-infrared polyester according to any one of claims 1 to 5, characterized in that: In step (3), the polycondensation reaction includes an esterification stage and a polycondensation stage performed sequentially; The reaction temperature of the esterification stage is 240-260° C., the reaction pressure is 0.18-0.25 MPa, and the reaction time is 3-4 hours; the reaction temperature of the polycondensation stage is 275-285° C., the reaction pressure is 60-200 Pa, and the reaction time is 2-3 hours.

7. The method for preparing the copolymerized antibacterial far-infrared polyester according to any one of claims 1 to 6, characterized in that: In step (3), the mass ratio of terephthalic acid, catalyst, type II modified far-infrared powder and ethylene glycol is 1: 0.0003-0.0005: 0.04-0.06: 0.6-0.7; Preferably, the catalyst is antimony glycolate.

8. The method for preparing the copolymerized antibacterial far-infrared polyester according to claim 7, characterized in that: In step (3), terephthalic acid, catalyst and type II modified far-infrared powder are sequentially added to ethylene glycol for slurry mixing, and the mixture obtained by mixing evenly is transferred to a reaction kettle for polycondensation reaction.

9. The method for preparing the copolymerized antibacterial far-infrared polyester according to any one of claims 1 to 8, characterized in that: In step (4), the process conditions of melt spinning include: The screw extrusion temperature is 250-270℃ in zone 1, 280-285℃ in zone 2, 280-290℃ in zone 3, and 285-295℃ in zone 4; The box temperature is 285-295°C, the spinning pressure is 10-12MPa, the side blowing speed is 0.4-0.5m / s, the oiling rate is 5%-15%, and the spinning speed is 4000-4500m / s; Preferably, the antibacterial far-infrared copolyester obtained in step (3) is vacuum dried at 120-130° C. for 6-8 hours and then melt-spun.

10. A copolymerized antibacterial far-infrared polyester, characterized in that: It comprises a polyester matrix, far-infrared powder and a Schiff base structure, wherein the surface of the far-infrared powder is connected with a modified group; the modified group on the surface of the far-infrared powder is connected to the Schiff base structure by a covalent bond, and the Schiff base structure is connected to the molecular chain of the polyester matrix by a covalent bond; Preferably, the copolymerized antibacterial far-infrared polyester is prepared by the preparation method of the copolymerized antibacterial far-infrared polyester according to any one of claims 1-9.

Citation Information

Patent Citations

  • Manufacturing technology for far-infrared polyester short fibers

    CN102560732B

  • A kind of manufacturing method of antibacterial far-infrared health-care polyester fiber

    CN105420835B

Cited By

  • Sixteen-hole multifunctional polyester staple fiber and preparation method thereof

    CN120485981A